The implications of direct participation for organisational commitment, job satisfaction and affective psychological well‐being: a longitudinal analysis. Issue 2 (20th June 2017) - Gallie, Duncan; Zhou, Ying; Felstead, Alan; Green, Francis; Henseke, Golo
Abstract: The article examines the implications of direct participation for employees' organisational commitment, job satisfaction and affective psychological well‐being. It focuses on both task discretion and organisational participation. Applying fixed effect models to nationally representative longitudinal data, the study provides a more rigorous assessment of the conflicting claims for the effects of participation that have hitherto been based primarily on cross‐sectional evidence. Further, it tests a range of mechanisms by which direct participation leads to improved employee outcomes. Contrary to the critical literature, it shows that even after controlling for unobserved individual heterogeneity, both forms of direct participation have positive effects for employees' organisational commitment and well‐being. The effects of task discretion are primarily direct, reflecting the intrinsic importance of personal control over the job task; in contrast, those of organisational participation derive to a greater extent from its indirect effect on the quality of working conditions.